Distribution, lipophilicity and tissue half-life as key factors in sulphonamide clearance from porcine tissues - Burmańczuk Artur; Osypiuk Monika; Polska Bożena; Kunicki Dominik; Kocik Marcin; Grzęda Karol; Markiewicz Włodzimierz; Yilmaz Oktay; Grabowski Tomasz (Journal of Veterinary Research)
Sulphonamides are some of the most widely used antimicrobial drugs in the treatment of bacterial diseases in pigs. The study was conducted to compare the total exposure of tissue to a group of active substances in a single formulation and evaluate the impact of the volume of distribution, lipophilicity and tissue half-life of sulfadimethoxine, sulphathiazole, sulphamethazine and sulphacetamide in two different veterinary drug formulations – Polisulfalent, which was preparation A, and Polisulfamid, which was preparation B.